2009
DOI: 10.2460/ajvr.70.4.522
|View full text |Cite
|
Sign up to set email alerts
|

Single- and multiple-dose pharmacokinetics of marbofloxacin after oral administration to rabbits

Abstract: OBJECTIVE-To determine the pharmacokinetics of marbofloxacin after oral administration every 24 hours to rabbits during a 10-day period. ANIMALS-8 healthy 9-month-old female New Zealand White rabbits. PROCEDURES-Marbofloxacin (5 mg/kg) was administered orally every 24 hours to 8 rabbits for 10 days. The first day of administration was designated as day 1. Blood samples were obtained at 0, 0.17, 0.33, 0.5, 0.75, 1, 1.5, 2, 3, 4, 5, 6, 8, 12, and 24 hours on days 1 and 10 of marbofloxacin administration. Plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In present study, mean values of elimination half-lives (t 1/2 ) were 4.62 ± 0.42 and 5.63 ± 0.60 h after single and repeated dose, respectively. Carpenter et al (2009) observed lower value of t 1/2 of 3.90 ± 0.00 h in rabbits after repeated oral administration of marbofloxacin. Whereas, higher value of t 1/2 of 7.77 ± 0.31 h was reported after repeated oral administration in cats (Albarellos et al, 2005).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…In present study, mean values of elimination half-lives (t 1/2 ) were 4.62 ± 0.42 and 5.63 ± 0.60 h after single and repeated dose, respectively. Carpenter et al (2009) observed lower value of t 1/2 of 3.90 ± 0.00 h in rabbits after repeated oral administration of marbofloxacin. Whereas, higher value of t 1/2 of 7.77 ± 0.31 h was reported after repeated oral administration in cats (Albarellos et al, 2005).…”
Section: Resultsmentioning
confidence: 66%
“…However, after six days, repeated oral administration of marbofloxacin in cats, higher value of C max (2.34 ± 0.98 µg/ml at 1.60 ± 1.20 h) was observed as compare to respective value of C max (1.78 ± 0.53 µg/ml at 1.61 ± 1.80 h), following single dose of drug (Albarellos et al, 2005). Carpenter et al (2009) also reported higher C max value of 2.56 ± 0.71 µg/ml at 1.40 ± 0.44 h in rabbits after repeated oral administration for 10 days as compare to respective value of 1.73 ± 0.35 µg/ml at 1.60 ± 0.94 h after single dose. The plasma concentrations of marbofloxacin of  0.38 ± 0.06 (after single dose) and  0.43 ± 0.07 g/ml (after repeated dose) were maintained up to 12 h after drug administration.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…13 The pharmacokinetics of marbofloxacin has been studied in many species, but few reports are available on its disposition in rabbits. [14][15][16] Interestingly, the terminal half-life of marbofloxacin was shorter when administered SC compared with either the intramuscular or the intravenous (IV) route, 16 although a very high bioavailability was identified for marbofloxacin when administered through the intramuscular and SC routes. 15,16 Fluoroquinolones exhibit concentration-dependent bactericidal activity.…”
Section: Antibacterial Agents _____________________ Marbofloxacinmentioning
confidence: 99%
“…Bacterial diseases, especially gram‐negative infections associated with Pasteurella multocida , Pseudomonas aeruginosa and Escherichia coli , are common in various organ systems of the rabbit, including the skin (Varga & Paterson, 2020), respiratory tract (Lennox & Mancinelli, 2020), gastrointestinal tract (Oglesbee & Lord, 2020), urinary tract and reproductive system (Di Girolamo & Selleri, 2020). Pharmacokinetic profiles for fluoroquinolones that have been, or are currently commercially available in rabbits, have been reported for enrofloxacin (Broome et al, 1991; Elmas et al, 2007), ciprofloxacin (Bashir et al, 2008; Hanan et al, 2000), marbofloxacin (Carpenter et al, 2009; Marín et al, 2013), danofloxacin (Fernández‐Varón et al, 2007), levofloxacin (Sitovs et al, 2020) and orbifloxacin (Marín et al, 2008; Watson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%